2011
DOI: 10.1016/j.febslet.2011.08.034
|View full text |Cite
|
Sign up to set email alerts
|

The endogenous siRNA pathway inDrosophilaimpacts stress resistance and lifespan by regulating metabolic homeostasis

Abstract: a b s t r a c tSmall non-coding RNAs regulate gene expression in a sequence-specific manner. In Drosophila, Dicer-2 (Dcr-2) functions in the biogenesis of endogenous small interfering RNAs (endo-siRNAs). We identified 21 distinct proteins that exhibited a P1.5-fold change as a consequence of loss of dcr-2 function. Most of these were metabolic genes implicated in stress resistance and aging. dcr-2 Mutants had reduced lifespan and were hypersensitive to oxidative, endoplasmic reticulum, starvation, and cold str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 43 publications
6
45
0
Order By: Relevance
“…These cellular defenses against TE activation include siRNA-directed induction and maintenance of repressive heterochromatin to prevent TE expression, and degradation of target transcripts. siRNA pathway mutants exhibit both an activation of TEs and a shortening of life span (15,24). Here we provide evidence that many heterochromatin genes and TEs do in fact increase expression with age in two different tissues.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…These cellular defenses against TE activation include siRNA-directed induction and maintenance of repressive heterochromatin to prevent TE expression, and degradation of target transcripts. siRNA pathway mutants exhibit both an activation of TEs and a shortening of life span (15,24). Here we provide evidence that many heterochromatin genes and TEs do in fact increase expression with age in two different tissues.…”
Section: Discussionmentioning
confidence: 67%
“…In addition to their effects of delaying age-related heterochromatin gene and TE silencing loss, both increased Sir2 expression and decreased Adar expression have been shown to extend life span in flies (21,25), whereas Dicer-2 and Ago2 mutants are short-lived (15,24). Given our findings presented earlier, we examined whether increased expression of Su(var)3-9 or Dicer-2 also have a positive effect on life span.…”
Section: Genetic Interventions That Affect Heterochromatin Structure mentioning
confidence: 99%
See 1 more Smart Citation
“…Chromatin immunoprecipitation and DNA fluorescence in situ hybridization experiments further demonstrate that both Ago-2 and Dcr-2 are integrated in the regulatory complex that causes RNA polymerase II pausing and play a role in the correct execution of the global transcriptional repression after heat-shock. Consistent with a role for the siRNA pathway in stress regulation, it was reported that dcr-2 mutants were more sensitive to different types of stresses such as toxic chemicals, starvation and cold shock, and had a reduced lifespan [196]. Furthermore, abnormal lipid and carbohydrate metabolism was associated with loss of Dcr-2 and comparative proteomics revealed changes in expression of proteins associated with cellular metabolism, stress resistance, cell cycle [196].…”
Section: Heat-shock Proteins and Stressmentioning
confidence: 68%
“…Consistent with a role for the siRNA pathway in stress regulation, it was reported that dcr-2 mutants were more sensitive to different types of stresses such as toxic chemicals, starvation and cold shock, and had a reduced lifespan [196]. Furthermore, abnormal lipid and carbohydrate metabolism was associated with loss of Dcr-2 and comparative proteomics revealed changes in expression of proteins associated with cellular metabolism, stress resistance, cell cycle [196]. During heat shock, Dcr-2 protein levels are reduced and dicing activity of long dsRNA substrates is diminished [197].…”
Section: Heat-shock Proteins and Stressmentioning
confidence: 82%